Pemanfaatan Super Bookashi MA-11 dan Biosaka Terhadap Pertumbuhan dan Hasil Padi (Oryza sativa L.) Varietas Inpari 10 - Ajang Maruapey; Yenni Asbur (Universitas Sebelas Maret, 2025)
In rice cultivation practices, the use of organic fertilizers such as super bokashi MA-11 and Biosaka offers a more sustainable and environmentally friendly solution compared to conventional chemical fertilizers. The aim of this study was to evaluate the effectiveness of the use of super bokashi MAS-11 and biosaka on the growth and yield of Inpari 10 rice varieties. The study was conducted in Klaru, Mariat, Sorong, Southwest Papua, from February to May 2024. The experiment was conducted using a two-factor Randomized Block Design and three replications. Super bokashi MA-11 organic fertilizer as the first factor was applied in four levels: S0 (no treatment), S1 (5 tons/ha), S2 (7 tons/ha), and S3 (9 tons/ha). Biosaka as the second factor consisted of three levels: B0 (no treatment), B1 (20 mL/5 L of water), B2 (40 mL/5 L of water), and B3 (60 mL/5 L of water). The results of the study showed that the super bokashi MA-11 dose of 9 tons/ha (S3) successfully increased the dry grain yield (GKP) of rice up to 6.48 tons/ha, while the application of Biosaka at a dose of 60 mL/5 L of water (B3) could increase the GKP yield of rice up to 5.98 tons/ha.